An empirical study on the relationship between government expenditure on education and economic growth in Malaysia - Chew, Xiao Chin (2013)
The main purpose of this study is to investigate the relationship between education and economic growth. The study is based on annually time series data range from period 1970 until 2010. The indicators for education are government operating expenditure and government development expenditure in education sector. Following the endogenous growth theory, log linear model is build based on Cobb Douglas production function. In order to answer the three objectives in this study, the tests been carried out included Augument Dikey Fuller test (ADF) test to test unit root, Ordinary Least Squares (OLS) test to estimate how dependent variable changes when there is an increase in independent variables, Johansen cointegration test to investigate the existence of long run relationship in the model and Granger causality test to determine the direction of causality between all variables. The finding of the study is consistent with most of the empirical studies and theory where there is a long run relationship between education and economic growth. Besides that, the estimated results show that operating expenditure is relatively bring more impact to gross domestic product compared to development expenditure. In addition, the empirical evidence demonstrates that operating expenditure exits bilateral causality relationship with economic growth